Pengaruh Pembelajaran Berbasis Masalah terhadap Disposisi Matematis dan Kemampuan Pemecahan Masalah Siswa - Gozali, Imam; Syamsuri, Syamsuri; Nindiasari, Hepsi; Fatah, Abdul (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2022)
Problem based learning on the mathematical disposition and problem solving abilities of students is the ability to think and mathematical attitudes that must be possessed by students. Through the application of problem-based learning, it is hoped that it can improve the problem solving ability of students' mathematical dispositions. This study was conducted to determine the effect of problem-based learning on problem-solving abilities on students' mathematical dispositions. The research design used is a quasi-experimental design, namely the pretest-posttest control group design with a population of all students of class X SMK Az-zahra in the academic year 2021/2022. Through purposive random sampling technique, the TKJ 3 class was obtained as the experimental class (n = 36) and the TKJ 2 class as the control class (n = 36). Collecting data using a test of problem solving ability and mathematical disposition. Data analysis was carried out descriptively and inferentially (Î± = 0.05). Based on data analysis, it is known that the increase in problem solving abilities of students who receiving problem..based learning is higher than students who receive conventional learning. The increase in the mathematical disposition of students who received problem-based learning was higher than students who received conventional..learning. so the conclusion is problem-based learning can improve problem-solving skills on students' mathematical dispositions.